(3ahGFO eSJNQLI ef TQM Ydi Hf QVhGf GdeUQi dcJGH LGdjfhS Edi CZdhbfs - (3ENJjGQ CHh LYaQ jhSa Hf CMeO , GHf MSOGis
(3ChdgG (B:s
(3RYe bhe Cf ZQV gPG GdcJGH gh GdJCJi deTaGA GdMejGJ abW , hGdCeQ Ydi NdGa eGRYeh ,dCfg de jSJhYH ajg PcQ LejY GdMejGJ s
(3BNQgG (B:s
(3cedJ GdahGFO GdeSJNQLI ef TQM GdCeQGV , GSJNQGL CHj LYaQ GHf MSOGi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQ CjVkG agQS GdWH HQbe (B22 " (3cJGH Edi CZdhbf (B"s
(3hGSe cJGH LGdjfhS (B:" (3cJGH Edi CZdhbf ai GdJGJi dTaGA GdCeQGV(B" (3hgh ebGdJGf Hjf ajgeG OdGFd GdCeQGV GdJi JYQa HgG bHd eOGhGJgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B174 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdWHs